2011
DOI: 10.3758/s13421-011-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Reading aloud pseudohomophones in Italian: Always an advantage

Abstract: In the present article, the lexical contribution to nonword reading was evaluated using Italian pseudohomophones that contained atypical letters or letter sequences. Pseudohomophones were read faster than orthographically matched nonwords in both mixed (Experiment 1) and pure (Experiment 2) lists; in addition, a base-word frequency effect was obtained in both conditions. The same pseudohomophone advantage was observed when nonwords without atypical letter sequences were mixed in the experimental list (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Such results revealed that audio-visual aids and CALI had positive educative and treatment effects on the performance levels of students of special needs, notably in matters concerning language components in general and sound system in particular. They also confirmed those of other studies undertaken on the same issue (Gilakjani, 2012;Peressotti & Colombo, 2012;Augustinova & Ferrand, 2012;Pike, 2012;Swimelar, 2013;Wild, 2013;Pérez-Bellido, et al, 2013;and SuHua, et al, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…Such results revealed that audio-visual aids and CALI had positive educative and treatment effects on the performance levels of students of special needs, notably in matters concerning language components in general and sound system in particular. They also confirmed those of other studies undertaken on the same issue (Gilakjani, 2012;Peressotti & Colombo, 2012;Augustinova & Ferrand, 2012;Pike, 2012;Swimelar, 2013;Wild, 2013;Pérez-Bellido, et al, 2013;and SuHua, et al, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
“…Using the Italian pseudo homophones that contained atypical letters or letter sequences in more complex items than those commonly employed within the information-processing approach, but still easier than those used in intelligence tests, Peressotti & Colombo (2012)'s study analyzed how the lexical contribution to non-word reading can be evaluated. The study involved analyzing the outcomes of three experiments and concluded that the Italian pseudo homophones did not benefit from an orthographic lexical contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Peressotti and Colombo [40] examined this in Italian using pseudohomophones that were orthographically often very strange (e.g., cjfra ) and similarly matched nonwords, with the idea being that using nonwords with strange sequences of letters meant that none of the effects they found could be due to orthographic similarities between pseudohomophones and the words that they sounded like. They also compared the results to more orthographically normal non-pseudohomophonic nonwords.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strange orthographic patterns used by Peressotti and Colombo [40], we presented their stimuli to CDP++. Not surprisingly, the model had a high error rate, since it simply could not produce a reasonable answer for some of the nonwords, such as when a –j was used as a vowel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation